Genomic Stock Structure of the Marine Teleost Tarakihi (Nemadactylus macropterus) Provides Evidence of Potential Fine-Scale Adaptation and a Temperature-Associated Cline Amid Panmixia - Papa, Yvan; Morrison, Mark A.; Wellenreuther, Maren; Ritchie, Peter A. (Frontiers in Ecology and Evolution, 2022)
Tarakihi (Nemadactylus macropterus) is an important fishery species that has a widespread distribution around New Zealand and off the southern coasts of Australia. However, little is known about whether the populations are locally adapted or genetically structured. To address this, we conducted whole-genome resequencing of 175 tarakihi from around New Zealand and Tasmania (Australia) to obtain a dataset of 7.5 million genome-wide and high-quality SNPs. Variant filtering, FST-outlier analysis, and redundancy analysis (RDA) were used to evaluate population structure, adaptive structure, and locus-environment associations. A weak but significant level of neutral genetic differentiation was found between tarakihi from New Zealand and Tasmania (FST = 0.0054–0.0073, P ≤ 0.05), supporting the existence of at least two separate reproductive stocks. No clustering was detected among the New Zealand populations (ФST < 0.001, P = 0.77). Outlier-based, presumably adaptive variation suggests fine-scale adaptive structure between locations around central New Zealand off the east (Wairarapa, Cape Campbell, and Hawke’s Bay) and the west coast (Tasman Bay/Golden Bay and Upper West Coast of South Island). Allele frequencies from 55 loci were associated with at least one of six environmental variables, of which 47 correlated strongly with yearly mean water temperature. Although genes associated with these loci are linked to various functions, the most common functions were integral components of membrane and cilium assembly. Projection of the RDA indicates the existence of a latitudinal temperature cline. Our work provides the first genomic insights supporting panmixia of tarakihi in New Zealand and evidence of a genomic cline that appears to be driven by the temperature gradients, together providing crucial information to inform the stock assessment of this species, and to widen the insights of the ecological drivers of adaptive variation in a marine species.